2011
DOI: 10.1590/s1677-04202011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant capacities in the flavedo tissue of two citrus cultivars under low temperature

Abstract: Antioxidants production is amongst the physiological responses of plants to protect their tissues from oxidative damages caused by chilling and freezing stresses. Indeed, cold tolerance of plants is related to production of reactive oxygen species (ROS) scavengers to combat oxidative stress. In this study, two citrus cultivars including Citrus sinensis 'Siavaraz' and Citrus limon 'Lisbon' grown at the north of Iran were examined to compare antioxidants changes including total flavonoid, total phenol and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
(41 reference statements)
3
11
0
3
Order By: Relevance
“…Citrus is the general term for plants belonging to the family Rutaceae 2 . Citrus fruits and derived products have beneficial impacts on the human health 3 . Hence, citrus fruits have attracted much attention because of its nutritional and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus is the general term for plants belonging to the family Rutaceae 2 . Citrus fruits and derived products have beneficial impacts on the human health 3 . Hence, citrus fruits have attracted much attention because of its nutritional and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Anthelmintic activity Citrus limon fruit empty juice sacs was investigated from Nagpur region of Maharashtra 6 . Comparative study of antioxidants changes including total flavonoid, total phenol and total antioxidant capacity of Citrus limon fruits grown at the north of Iran were examined 3 . Determination of phenolic contents and total antioxidant activity of citrus lemon juice and peel extracts was reported from Bosnia and Herzegovina 7 .Yield, fruit quality, economic feasibility and water productivity of citrus limon plants were evaluated 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Anthelmintic activity Citrus limon were investigated 2,3,4 . Comparative study of antioxidants changes including total flavonoid, total phenol and total antioxidant capacity of Citrus limon fruits grown at the north of Iran were examined 5 . Antimicrobial activity of juice in ripens and unripe forms of Citrus limon were studied 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flavonoid compounds have activities that are similar to carotenoids [2]. However, studies of citrus cultivars and fruit development have revealed that the contents differed for carotenoids [3,4], flavonoid [5,6], phenolic compounds [5][6][7][8], and ascorbic acid [6]. Further, the flavonoid and phenolic contents were affected by environmental conditions [5].…”
Section: Introductionmentioning
confidence: 99%